Per-Vaginal Delivery of Dicephalic Perosomus Elumbis Monster by Partial Fetotomy in a Cow - Panihar, Sandeep; Pandey, Anand Kumar; Pradeep; Singh, Gyan; Kumar, Rakesh; Garbhit (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Dystocia, a challenging condition in obstetrics, can arise  from various causes, including fetal monsters with  structural abnormalities. Congenital fetal monstrosities are  not uncommon clinical findings in dairy cattle where multiple  anatomical defects could be found in the fetal monsters.  Although, the exact etiologies for these conditions are not  known but their clinical presentation sometimes causes life  threatening condition to the dam along with the loss of calf  crop. The most common group of monsters is conjoined twins  which arise from incomplete division from fertilized ovum.  Dicephalic is described as an abnormality of incomplete  separation of heads resulting from twinning in animals.  Perosomus elumbis is a rarely occurring congenital condition  characterized with partial or complete agenesis of lumbar,  sacral and coccygeal vertebrae and ankylosis of hind limbs  (Son, 2008). The conspicuous feature for the obstetrician is  the rigidity of the posterior limbs (Arthur et al., 2001). Double  headed calf represent a case of absolute fetal oversize with  subsequent provoke of dystocia in animals. The present  report represents the successful per-vaginal delivery of  dicephalic perosomus elumbis monster by partial fetotomy  in a cow.
Keywords: coccygeal vertebrae; obstetrician; per-vaginal delivery; fetotomy in a cow.